Disruption of Clever-1 for Novel Anticancer Immunotherapy - Viitala, Miro (fi=Turun yliopisto|en=University of Turku|, 2016)
The progression of cancer is dependent on the quality of the immune response elicited by the tumour. Typically, proinflammatory immune responses restrain and anti-inflammatory immune responses promote the progression of cancer. The immunosuppression caused by anti-inflammatory leukocytes, such as regulatory T cells and alternatively activated macrophages, is a major obstacle in the successful treatment of cancer. Clever-1 is a multifunctional protein expressed by a subset of human monocytes and alternatively activated, or M2, macrophages. In these macrophages, Clever-1 is involved in receptor-mediated endocytosis, intracellular sorting, and transcytosis. Clever-1 is also expressed on lymphatic and vascular endothelia, where it mediates the trafficking of leukocytes from the lymph or blood into tissues. Lymphatics and macrophages expressing Clever-1 have been detected in human cancers, and high numbers of Clever-1-positive macrophages correlate with poorer prognoses in advanced colorectal cancer. By using specific antibodies to interfere with the function Clever-1, we have recently demonstrated that Clever-1 antibody treatment limits the progression of cancer in animal models of melanoma and lymphoma. According to these results, the antibody-mediated interference of Clever-1 both before and after cancer cell implantation limits tumour growth and metastasis. However, the molecular mechanisms by which Clever-1 regulates the phenotype and function of tumour-associated macrophages during this process are very poorly understood. The data presented in this master’s thesis reveal novel molecular mechanisms employed by Clever-1 to regulate the function of M2 macrophages and suggest that Clever-1 antibody treatment may have immunotherapeutic potential in the treatment of breast cancer. According to the obtained results, Clever-1 promoted intracellular signal transduction through the anti-inflammatory mTORC1 complex in M2 macrophages. In accordance, the antibody-mediated interference of Clever-1 induced a proinflammatory response from M2 macrophages by increasing the production and secretion of TNF-α, a major mediator of inflammation. Furthermore, combinatorial antibody-mediated interference of Clever-1 and the immune checkpoint protein PD-1 decreased the relative amount of anti-inflammatory tumour-associated macrophages, thereby likely promoting a more proinflammatory milieu within the tumour microenvironment. Additionally, combinatorial Clever-1 and PD-1 antibody treatment appeared to limit tumour growth and metastasis also in a mouse model of triple-negative breast cancer.

Syövän eteneminen riippuu siitä, minkälaisen immuunivasteen kasvain aiheuttaa. Tavallisesti tulehdusta lisäävä eli proinflammatorinen immuunivaste estää ja tulehdusta vähentävä eli anti-inflammatorinen immuunivaste edistää syövän etenemistä. Anti-inflammatoristen valkosolujen, kuten säätelijä- T-solujen ja M2-makrofagien, aiheuttama immuunivasteen vaimennus on yksi onnistuneen syöpähoidon suurimmista esteistä. Clever-1 on monitoiminen proteiini, jota ilmentää ihmisen monosyyttien ja M2-makrofagien alaluokka. Näissä makrofageissa Clever-1 osallistuu reseptorivälitteiseen endosytoosiin, solunsisäiseen lajitteluun ja transsytoosiin. Clever-1:tä ilmennetään myös imu- ja verisuonten endoteelissä, missä se välittää valkosolujen kulkeutumista imunesteestä ja verestä kudoksiin. Ihmisen syövissä on havaittu Clever-1:tä ilmentäviä imusuonia ja makrofageja, ja esimerkiksi edenneessä peräsuolen syövässä suuri määrä Clever-1-positiivisia makrofageja korreloi heikomman ennusteen kanssa. Häiritsemällä Clever-1:n toimintaa siihen kohdennetuilla vasta-aineilla ryhmämme on hiljattain osoittanut, että Clever-1-vasta-ainehoito hidastaa syövän etenemistä melanooman ja lymfooman eläinmalleissa. Tulosten perusteella Clever-1:n toiminnan häiritseminen vasta-aineella sekä ennen syöpäsolujen istutusta että sen jälkeen vähentää kasvaimen kasvua ja etäpesäkkeiden muodostumista. Mekanismi, jolla Clever-1 säätelee kasvaimeen liittyvien makrofagien fenotyyppiä ja toimintaa kasvaimen kasvun ja etäpesäkkeiden muodostumisen aikana, on kuitenkin vielä erittäin puutteellisesti tunnettu. Tässä pro gradu -työssä esitetyt tulokset paljastavat uusia molekulaarisia mekanismeja, joilla Clever-1 säätelee M2-makrofagien toimintaa, ja antavat viitteitä Clever-1-vasta-ainehoidon mahdollisesta immunoterapeuttisesta tehosta myös rintasyövän hoidossa. Saatujen tulosten perusteella Clever-1 lisäsi anti-inflammatorisen mTORC1-kompleksin kautta tapahtuvaa solunsisäistä signaalitransduktiota M2-makrofageissa. Vastaavasti Clever-1:n toiminnan häiritseminen vasta-aineella aiheutti M2-makrofageissa proinflammatorisen vasteen lisäämällä keskeisen tulehduksenvälittäjäaineen tuumorinekroositekijä- α:n tuotantoa ja erittymistä. Lisäksi yhdistelmähoito Clever-1-:tä ja PD-1-säätelijäproteiinia estävällä vasta-aineella vähensi kasvaimeen liittyvien anti-inflammatoristen makrofagien suhteellista osuutta ja siten todennäköisesti edisti proinflammatorista tulehdusvastetta kasvaimen sisällä. Sen lisäksi yhdistelmähoito Clever-1- ja PD-1-vasta-aineella näytti estävän kasvaimen kasvua ja etäpesäkkeiden muodostumista triplanegatiivisen rintasyövän hiirimallissa.